Analisis Pengaruh Faktor Emosional, Kualitas Layanan, Serta Fasilitas Terhadap Kepuasan Pelanggan Penjilidan Express Di Kecamatan Kedungwaru, Kabupaten Tulungagung. - Muhammad Fahri Bachtiar; Meilia Wulandari; Nurhana Nufita Sari; Aris Fauzi Nurfarichi; Nadia Roosmalita Sari (JMB : Jurnal Manajemen dan Bisnis, 2023)
In facing intense business competition, business people must try to create customer satisfaction, because this is important for creating customer loyalty and Word of Mouth. This study is intended to prove and analyze whether or not there is an influence between emotional, service quality, and facilities on Penjilidan Express customer satisfaction in Kedungwaru District, Tulungagung Regency. This research is associative with a quantitative approach. Primary data was used in this study, and a questionnaire was chosen as the technique for collecting data. The sampling technique is non-probability sampling in the form of accidental sampling. All customers who have used Penjilidan Express services in Kedungwaru District, Tulungagung Regency will become the study population. With the lameshow technique, 100 respondents were obtained to be used as samples. Multiple linear regression analysis is a technique used for data analysis. Data analysis begins by conducting data quality tests including validity and reliability tests, followed by classical assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests, then multiple linear regression tests, F tests (combined), T tests (partial), and the last is the test of the coefficient of determination (R2). The study findings prove that emotional variables and service quality have a positive and significant effect on customer satisfaction, but facilities do not have a significant effect on customer satisfaction. Simultaneously emotional variables, service quality, and facilities have a positive and significant influence on Penjilidan Express customer satisfaction in Kedungwaru District, Tulungagung Regency with a proportion of 49.2%.